2013
DOI: 10.1097/mph.0b013e31828d5e6a
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Hematopoietic Cell Transplantation Clinical Trial Participation of African American and Black Youth With Sickle Cell Disease and Their Parents

Abstract: African-Americans and Blacks have low participation rates in clinical trials and reduced access to aggressive medical therapies. Hematopoietic cell transplantation (HCT) is a high-risk investigational but potentially curative therapy for sickle-cell disease (SCD), a disorder predominantly seen in African-Americans. We conducted focus groups to better understand participation barriers to HCT clinical trials for SCD. Nine focus groups of youth with SCD (n=10) and parents (n=41) were conducted at three sites repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…Transplant teams may also consider factors not assessed here for making decisions to offer transplantation to patients, such as the resources available to families for decision making and patient factors such as medication adherence, social support systems, and reluctance to participate in clinical trials involving transplantation. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Transplant teams may also consider factors not assessed here for making decisions to offer transplantation to patients, such as the resources available to families for decision making and patient factors such as medication adherence, social support systems, and reluctance to participate in clinical trials involving transplantation. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, far less than 1% of the SCD population in the US has received a transplant. Many barriers to transplant exist, and these are detailed in other reports 6, 78 . A key barrier is a prevailing assumption that HCT is risky and carries a mortality rate that exceeds mortality experienced with a supportive care approach.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies addressing this topic have focused on the factors that affect the decisions of children/adolescents with SCD or their parents. 813 Yet a large body of literature exists that examines the determinants of African-American participation in research generally. This research has found an important role for the attitudes that individuals have about clinical research.…”
Section: Introductionmentioning
confidence: 99%